Surfactant-mediated thioglycosylation of 1-hydroxy sugars in water. Issue 4 (6th January 2021) - Ratthachag, Trichada; Buntasana, Supanat; Vilaivan, Tirayut; Padungros, Panuwat
Abstract : Dodecyl benzenesulfonic acid (DBSA)-mediated thioglycosylation in water provided thioglycosides without open-chain dithioacetal sugars, which are common by-products when performing reactions in organic solvent. Abstract : Thioglycosides are an important class of sugars, since they can be used as non-ionic biosurfactants, biomimetic glycosides, and building blocks for carbohydrate synthesis. Previously, Brønsted- or Lewis-acid-catalyzed dehydrative glycosylations between a 1-hydroxy sugar and a thiol have been reported to yield open-chain dithioacetal sugars as the major products instead of the desired thioglycosides. These dithioacetal sugars are by-products derived from the endocyclic bond cleavage of the thioglycosides. Herein, we report dehydrative glycosylation in water mediated by a Brønsted acid–surfactant combined catalyst (BASC). Glycosylations between 1-hydroxy furanosyl/pyranosyl sugars and primary, secondary, and tertiary aliphatic/aromatic thiols in the presence of dodecyl benzenesulfonic acid (DBSA) provided the thioglycoside products in moderate to good yields. Microwave irradiation led to improvements in the yields and a shortening of the reaction time. Remarkably, open-chain dithioacetal sugars were not detected in the DBSA-mediated glycosylations in water. This method is a simple, convenient, and rapid approach to produce a library of thioglycosides without the requirement of anhydrous conditions. Moreover, this work also provides an excellent example of complementary reactivity profiles of glycosylation in organic solvents and water.